Identification of disease-stage therapeutic responses of mesenchymal stromal cells retrieved from murine osteoarthritic joints - Ivanovska, Ana; Mancuso, Patrizio; Burke, Amy; Hennessy, Conor; Raman, Swarna; Dooley, Claire; McLoughlin, Steven; Shaw, Georgina; Mukeria, Eka; Reilly, Jamie; O’Brien, Aisling; Ritter, Thomas; et al. (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveOsteoarthritis (OA) is a widespread and debilitating joint disease characterized by synovial inflammation, cartilage degeneration, and chronic joint pain. Mesenchymal stromal cells (MSCs) have shown therapeutic efficacy for many diseases with a strong inflammatory profile, including OA. However, the disease-specific mechanisms of action underpinning the effects of post-local MSC delivery remain unaddressed. In this study, we aimed to characterize the disease-induced profile of MSCs following exposure to the in vivo osteoarthritis environment.MethodsMurine syngeneic GFP + bone marrow-derived MSCs (BM-MSCs) were delivered via intra-articular injection in a mouse collagenase-induced osteoarthritis (CIOA) model (n = 8). BM-MSCs were retrieved by cell sorting on days 14 and 56, following whole mouse knee digestions. The retrieved cells were expanded in culture and characterized based on their phenotype, immunomodulatory effects on lymphocytes and macrophages, and transcriptomic profile.ResultsRetrieved BM-MSCs (1.33%) had minimal effects on lymphocyte proliferation but induced macrophage anti-inflammatory activity. Surviving retrieved BM-MSCs activated various pathways, with their secretome impacting immune system regulation and extracellular matrix organization, correlating with the disease stage. Data comparing the transcriptomic profiles of retrieved and in vitro-licensed BM-MSCs suggested a chondroprogenitor profile and identified BRINP3 as a novel factor in MSC function for potential OA modulation.ConclusionThe beneficial effects of BM-MSCs in OA post-local delivery could be attributed to a specific subset of cells able to resist the micro-inflammatory milieu and contribute to cartilage healing and suppression of associated synovial inflammation. Furthermore, data suggest a paradigm of environmentally guided plasticity associated with MSCs upon local delivery in both early and late OA.